Integrin β1 activation by micro-scale curvature promotes pro-angiogenic secretion of human mesenchymal stem cells. Issue 35 (29th August 2017) - Li, Zhengdong; Wang, Weiwei; Xu, Xun; Kratz, Karl; Zou, Jie; Lysyakova, Liudmila; Heuchel, Matthias; Kurtz, Andreas; Gossen, Manfred; Ma, Nan; Lendlein, Andreas
Abstract : A cell culture substrate with micro-scale surface curvature promotes β1 integrin activation and pro-angiogenic secretion of mesenchymal stem cells. Abstract : Fine tuning of the substrate properties to modulate the function of mesenchymal stem cells (MSCs) has emerged as an attractive strategy to optimize their therapeutic potential. In the context of the mechanotransduction process, the conformational change of integrin (integrin activation) plays a critical role in perceiving and transmitting various signals. In this study, polymeric cell culture inserts with defined bottom roughness were fabricated as a model system for cell cultivation. We showed that the conformational change of integrin and its downstream signaling cascade of human adipose-derived mesenchymal stem cells (hADSCs) could be modulated by the curvature of the cell–material interface. The curvature of the substrate surface with a roughness in the size range of a single cell could strongly increase the high-affinity β1 integrin level of hADSCs without alteration of the total β1 integrin level. Further, the integrin downstream FAK/ERK and Rho/ROCK pathways were activated and resulted in upregulated VEGF secretion of hADSCs. A conditioned medium on such a surface exhibited a strong pro-angiogenic effect, with an increased formation of the tubular structure, a higher migration velocity of endothelial cells and an enhanced blood vessel density in an e x vivo hen's egg test-chorioallantoic membrane (HET-CAM). These results highlighted the clinical potential to manipulate the topographic features of the cell culture substrate, whereby to regulate integrin affinity states and further control MSC functions.